2014
DOI: 10.1002/poc.3325
|View full text |Cite
|
Sign up to set email alerts
|

Halogen bond symmetry: the N–X–N bond

Abstract: Halogen bonding is the attractive interaction of an electrophilic region of a halogen with a nucleophile. Its geometry, energy, and dominantly electrostatic nature resemble that of the hydrogen bond. Halogen bond strength critically depends on the electron deficiency of the halogen. Accordingly, halonium ions that bear a formal positive charge are the strongest halogen bond donors known so far. Halonium ions, similar to H + , are capable of simultaneously interacting with two Lewis bases. The structure and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
148
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 87 publications
(156 citation statements)
references
References 111 publications
(167 reference statements)
7
148
0
1
Order By: Relevance
“…[38][39][40] Most of this data is structural in nature and derives from crystal studies, as recently summarized by Troff et al 41 The N-X XB bond in halosuccinimides [42][43][44] shows up as a short intermolecular contact. [38][39][40] Most of this data is structural in nature and derives from crystal studies, as recently summarized by Troff et al 41 The N-X XB bond in halosuccinimides [42][43][44] shows up as a short intermolecular contact.…”
Section: Introductionmentioning
confidence: 99%
“…[38][39][40] Most of this data is structural in nature and derives from crystal studies, as recently summarized by Troff et al 41 The N-X XB bond in halosuccinimides [42][43][44] shows up as a short intermolecular contact. [38][39][40] Most of this data is structural in nature and derives from crystal studies, as recently summarized by Troff et al 41 The N-X XB bond in halosuccinimides [42][43][44] shows up as a short intermolecular contact.…”
Section: Introductionmentioning
confidence: 99%
“…Koskinen et al has recently described analogous [S-I-S] + complexes in the solid state [126]. Three-center halogen bonds were reviewed [127]. Beer et al reported the covalency of halogen bonds in a catenane-based receptor system in various solvents [128].…”
Section: Addendummentioning
confidence: 98%
“…Such systems can be seen as the simultaneous interaction of a formally positively charged halogen with two halogen bond acceptors of comparable Lewis base strength in a linear fashion. This linear geometry is enforced by the antiparallel lobes of the empty p-orbital of the halogen, forming two "p-holes" framed by the negative belt of electron density of its filled p-orbitals (p x 2 p y 2 p z 0 ) [127]. Thus, the halogen bond donor of three-center bonds possesses analogous anisotropic electron distribution to that of two-center bonds.…”
mentioning
confidence: 97%
“…The jΔ 15N coord j of the complex indicates weak interaction (3 ppm) of the pyridine that is coordinating to N-fluoropyridinium (0 ppm, 235). Overall, the interaction strength order I > Br > Cl ) F is shown for the [NdXdN] + halogen bonds by both NMR and DFT [67,69,148,152], with the covalent character of the static, symmetric [N-X-N] + complexes increasing in the order Cl > Br > I.…”
Section: Halogen Bond Complexesmentioning
confidence: 99%
“…The three-centered [N-X-N] + halogen bond comprising a positive halogen(I) and simultaneously interacting with two electron donors is regarded as a specific subclass showing especially strong interactions [148,149]. Bis(pyridine)-based [N-I-N] + and [N-Br-N] + complexes, encompassing bromine(I) or iodine(I) as electron acceptor resembling the coordination complexes of Ag(I), for example, are present as static and symmetric structures (Fig.…”
Section: Halogen Bond Complexesmentioning
confidence: 99%